2014
DOI: 10.3892/mmr.2014.2070
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of resveratrol on adjuvant arthritis rats with abnormal immunological function via the reduction of cyclooxygenase-2 and prostaglandin E2

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease with unknown etiology. The present study investigated the anti-inflammatory effect of resveratrol on rats with adjuvant arthritis (AA) with abnormal immunological function via the reduction of cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2). AA model rats were established by injection of complete Freund's adjuvant and alterations in the rats secondary paw swelling and the polyarthritic scores were observed. Pathological examination of joint tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Also, they are in accordance with the recent studies that reported resveratrol showed significant cerebroprotective action against global cerebral ischemic/ reperfusion injury mediated by an antioxidant and anti-inflammatory mechanisms, and manifested as a significant reduction in oxidative stress markers as MDA, and inflammatory biomarkers as TNF-α, IL-6 and 10 and MPO enzymes [69,70]. Moreover, the laboratory and histological results of present study, are in agreement with other recent experimental study reported that the articular cartilage degeneration with synovial hyperplasia and inflammatory cell infiltration was significantly suppressed with also, a significant reduction in serum levels of COX-2 and PGE2 in adjuvant arthritic rats treated with resveratrol and suggested that resveratrol has a significant antiinflammatory effects; mediated by its ability to reduce the production of inflammatory biomediators COX-2 and PGE2 [71].…”
Section: Discussionsupporting
confidence: 93%
“…Also, they are in accordance with the recent studies that reported resveratrol showed significant cerebroprotective action against global cerebral ischemic/ reperfusion injury mediated by an antioxidant and anti-inflammatory mechanisms, and manifested as a significant reduction in oxidative stress markers as MDA, and inflammatory biomarkers as TNF-α, IL-6 and 10 and MPO enzymes [69,70]. Moreover, the laboratory and histological results of present study, are in agreement with other recent experimental study reported that the articular cartilage degeneration with synovial hyperplasia and inflammatory cell infiltration was significantly suppressed with also, a significant reduction in serum levels of COX-2 and PGE2 in adjuvant arthritic rats treated with resveratrol and suggested that resveratrol has a significant antiinflammatory effects; mediated by its ability to reduce the production of inflammatory biomediators COX-2 and PGE2 [71].…”
Section: Discussionsupporting
confidence: 93%
“…Resveratrol has been shown to reduce the expression of MMP and RANKL from RA‐FLSs . Moreover, anti‐arthritic potentials have been shown in in vivo settings (various experimental arthritis models) . Riveiro‐Naveira et al have reported that resveratrol reduces the severity of arthritis and joint swelling in the CIA model.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit arthritis, intra-articular injection of RES dramatically reduced cartilage destruction [250]. On the other hand, in various models of experimental arthritis oral administration of RES reduced severity of disease, dampening release of proinflammatory cytokines, even including IL-17 [108,251,252].…”
Section: Allergy and Autoimmune Diseasesmentioning
confidence: 99%